High-frequency organic rectifiers through interface engineering. (20th September 2017) - Kang, Chan-mo; Shin, Hyeonwoo; Lee, Changhee
Abstract: Abstract : The demand for high-frequency (HF) and low-cost rectifiers has encouraged many researchers to investigate organic rectifiers. Recently, organic rectifiers with enhanced intrinsic carrier mobility and charge injection efficiency have enabled operating frequencies to reach up to a gigahertz (GHz). The metal/organic and organic/organic interfaces have played a significant role in determining the electrical properties of the organic rectifiers. In this prospective article, we review the structure of organic rectifiers and present the current state-of-the-art to attain their HF performance. We discuss methods for improving their electrical properties using interface engineering and present future prospects for practical use of GHz-operable organic rectifiers.